Unions and investment in intangible capital - Gabriele Cardullo; Giovanni Sulis (IZA World of Labor, 2023)
Although coverage of collective bargaining agreements has been declining for decades in most countries, it is still extensive, especially in non-Anglo-Saxon countries. Strong unions may influence firms' incentives to invest in capital, particularly in sectors where capital investments are sunk (irreversible), as in research-intensive sectors. Whether unions affect firms' investment in capital depends on the structure and coordination of bargaining, the preference of unions between wages and employment, the quality of labor-management relations, the structure of corporate governance, and the existence of social pacts, among other factors.
Keywords: J51; J52; E22; L60; 330; unions; coverage; collective bargaining; investment; R&D; sunk capital